THE IMPORTANCE OF COMMUNICATIVE APPROACH IN TEACHING ENGLISH CLASSES - Kushakova Nodira Odilovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the significant role of communicative approach in teaching English to students. The main purposes are: to connect people together in, order to create opportunity, and awareness, to love other cultures and places to use a language. Practical part includes use of authentic materials, picture strips, information gap activity, language games, pair work and group work.